Knowing the law avoids medico-legal problems - Jahn Kassim, Puteri Nemie (2012)
There is also an increased interest amongst the nursing profession to know about the legal principles applicable to their practice. In order to be responsible, the nursing profession should be made aware of the legal principles governing their profession. Ignorance of the law is by no means a defence for anyone. The increase in litigation as well as judicial and legislative intervention in most profession has made it essential for the nursing profession to be more knowledgeable in legal matters and anxious as to the extent of their accountability to their patients. Knowledge of and adherence to the law is an imperative professional responsibility.